a) 8x- [2[tex] x^{2} [/tex] + 3x- ( 17- 4[tex] x^{2} [/tex] +5x -10)]
= 8x - [2[tex] x^{2} [/tex] +3x- (7- 4[tex] x^{2} [/tex] +5x)]
= 8x- (2[tex] x^{2} [/tex] + 3x- 7 +4[tex] x^{2} [/tex] -5x)
= 8x- (6[tex] x^{2} [/tex] -2x -7)
= 8x- 6[tex] x^{2} [/tex] +2x +7
= 10x -6[tex] x^{2} [/tex] +7
b) 13[tex] x^{2} [/tex] -(6x-5[tex] x^{2} [/tex] ) - {[3- 11x- (2- 5[tex] x^{2} [/tex] -7x )]}
= 13[tex] x^{2} [/tex] -6x +5[tex] x^{2} [/tex] -[(3- 11x -2 +5[tex] x^{2} [/tex] +7x)]
= 18[tex] x^{2} [/tex] -6x -(1 +18x +5[tex] x^{2} [/tex] )
= 18[tex] x^{2} [/tex] -6x -1 -18x -5[tex] x^{2} [/tex]
= 13[tex] x^{2} [/tex] -24x -1